Peningkatan Hasil Belajar Pecahan Senilai dengan Model Problem Based Learning (PBL) di Kelas IV Sekolah Dasar - Dewi Sasrina; Melva Zainil (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The objective of this research is to describe an integrated thematic learning process improvement to the model of problem based learning in fourth grade elementary school 14 Gadut Tilatang Kamang. The approach used in this research is qualitative and quantitative. The type of research is Classroom Action Research. The research data were obtained from lesson plan observation sheets, teacher aspects, student aspects and test sheets. The research aspects of the teacher first cyclethe average value of 86% with good qualification, in the second cycle to 93% with excellent qualifications. Aspects of the students' first cycle the average value of 86% with good qualification,in the second cycle to 93%, with excellent qualifications. The student learning outcomes first cycle with an average value of 81, increased in the second cycle to 93. This the model of problem based learning can enhance the learning process and student learning outcomes.